1991
DOI: 10.1111/j.1744-6570.1991.tb00693.x
|View full text |Cite
|
Sign up to set email alerts
|

Cultural Relativity in Action: A Comparison of Self‐ratings Made by Chinese and U.S. Workers

Abstract: Using a sample of 982 leader-subordinate dyads drawn from nine different organizations in the Republic of China (i.e., Taiwan), self-ratings of performance were compared with supervisory ratings of subordinate performance. Results indicated that Chinese employees rated their job performance less favorably than did their supervisors (i.e., they exhibited a modesty bias). This modesty bias occurred relatively uniformly across gender, various educational levels, and age groups. These results are contrary to the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
190
3
5

Year Published

1993
1993
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 229 publications
(207 citation statements)
references
References 29 publications
9
190
3
5
Order By: Relevance
“…In contrast, self-report surveys suggest that Japanese workers may express less commitment to their organizations (e.g., Cole, 1979;Luthans, McCaul, & Dodd, 1985;Near, 1989), and these results do not seem attributable to modesty response bias (Farh, Dobbins, & Cheng, 1991;Lincoln & Kalleberg, 1985;Yu & Murphy, 1993). Previous research (Abrams et al, 1998) also revealed cross-cultural differences in the impact of subjective normative pressures on workers in Japan versus the UK, consistent with the relatively greater levels of interdependence in Japanese culture (cf.…”
Section: Organizational Type and Cultural Differencesmentioning
confidence: 84%
“…In contrast, self-report surveys suggest that Japanese workers may express less commitment to their organizations (e.g., Cole, 1979;Luthans, McCaul, & Dodd, 1985;Near, 1989), and these results do not seem attributable to modesty response bias (Farh, Dobbins, & Cheng, 1991;Lincoln & Kalleberg, 1985;Yu & Murphy, 1993). Previous research (Abrams et al, 1998) also revealed cross-cultural differences in the impact of subjective normative pressures on workers in Japan versus the UK, consistent with the relatively greater levels of interdependence in Japanese culture (cf.…”
Section: Organizational Type and Cultural Differencesmentioning
confidence: 84%
“…For example, parents, as the primary verbal community early in life, might be one important social influence on self-evaluation. It is interesting to note, therefore, that American parents consistently overestimate their children's abilities (Gretarsson & Gelfand, 1988;Heriot & Schmickel, 1967;Miller, Manhal, & Mee, 1991 Svenson, 1981), and Chinese employees tend to rate their job performance more realistically (Fahr, Dobbins, & Cheng, 1991). Similarly, American students, who score relatively low on mathematics achievement tests, tend to judge their math skills positively, whereas Chinese students, who score relatively high, tend to judge their skills less positively (Stevenson, Chen, & Lee, 1993;Stevenson, Lee, & Stigler, 1986).…”
Section: Discussionmentioning
confidence: 99%
“…In extreme versions, neither of these perspectives seems to be well equipped to incorporate factors (such as signal probability effects) that are capable of shifting bias momentarily from "self-enhancing" to "self-effacing" and thus are likely to be present in the self-evaluation of normal individuals. Moreover, it is unclear whether these views can accommodate possible cultural differences in self-evaluation biases (Fahr, Dobbins, & Cheng, 1991;Stevenson, Chen, & Lee, 1993). It seems likely that any viable theory of behavioral self-regulation would have to take into account the results of research on the situational determinants of self-evaluation, as would occur within a psychophysical framework.…”
Section: Discussionmentioning
confidence: 99%